Single-cell eQTL mapping of human endogenous retroviruses reveals cell type-specific genetic regulation in autoimmune diseases - Fan Zhu; Yi Liu; Jiehao Lei; Xinxing Li; Zexu Jiang; Xuan Dong; Ying Gu; Young Li (Nature Communications)
Abstract Human endogenous retroviruses constitute a significant portion of the human genome and play complex roles in gene regulation and disease processes. However, the expression pattern and disease associations of specific retroviral loci remain pooly understood. This study examines the expression and regulatory mechanisms of these retroviral elements in immune cells. Utilizing single-cell RNA sequencing data from peripheral blood mononuclear cells, we identify 41,460 expressed retroviral loci, with 1936 showing cell type-specific expression. We further detect 3463 conditionally independent expression quantitative trait loci linked to retroviral elements, highlighting their potential role in mediating genetic variants and disease associations. Notably, these retroviral sequences associate significantly with autoimmune diseases, with specific loci demonstrating pleiotropic associations with disease-related genes. Our findings suggest that these elements are not merely genomic remnants but active participants in cellular regulation and disease progression. This work advances understanding of human-retroviral coevolution and highlights potential therapeutic targets in immune disorders.